2015
DOI: 10.1161/hypertensionaha.114.03346
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Somatic Mutations in Chinese Patients With Aldosterone-Producing Adenoma

Abstract: Recent studies have shown that somatic mutations in the KCNJ5, ATP1A1, ATP2B3, and CACNA1D genes are associated with the pathogenesis of aldosterone-producing adenoma. Clinical profile and biochemical characteristics of the mutations in Chinese patients with aldosterone-producing adenoma remain unclear. In this study, we performed DNA sequencing in 168 Chinese patients with aldosterone-producing adenoma and found 129 somatic mutations in KCNJ5, 4 in ATP1A1, 1 in ATP2B3, and 1 in CACNA1D. KCNJ5 mutations were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
78
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(88 citation statements)
references
References 31 publications
8
78
1
1
Order By: Relevance
“…We first confirmed previous findings showing a high prevalence of the KCNJ5 gene (76.3%) in Japanese patients with APAs after the addition of recent cases [7,[11][12][13]. In addition, Kitamoto et al reported a prevalence of 69.4% in Japanese [31], 59.5% in Taiwanese [29], 71.2% in Korean [30], and 76.8% in Chinese patients with APAs [28]. Although the reason for the higher prevalence in Japan remains unclear, a recent meta-analysis of somatic KCNJ5 mutations in APAs suggested that the apparent higher rate of KCNJ5 mutations in Japan and China might be related to the different protocols employed for patient selection or sodium intake [27].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We first confirmed previous findings showing a high prevalence of the KCNJ5 gene (76.3%) in Japanese patients with APAs after the addition of recent cases [7,[11][12][13]. In addition, Kitamoto et al reported a prevalence of 69.4% in Japanese [31], 59.5% in Taiwanese [29], 71.2% in Korean [30], and 76.8% in Chinese patients with APAs [28]. Although the reason for the higher prevalence in Japan remains unclear, a recent meta-analysis of somatic KCNJ5 mutations in APAs suggested that the apparent higher rate of KCNJ5 mutations in Japan and China might be related to the different protocols employed for patient selection or sodium intake [27].…”
Section: Discussionsupporting
confidence: 90%
“…The overall prevalence of KCNJ5 mutations was reported to be between 37 and 47% in European studies [27]. The KCNJ5 mutation rate was higher in Asian countries: China (76.8%) [28], Taiwan (59.5%) [29], Korea (71.2%) [30] and Japan (Kitamoto et al 69.4% [31] and the present study 76.3%), than in European countries. Mutated APA patients in Europe were more often females, whereas no gender difference was observed in Taiwan and Japan (China; 43.6% in males, Taiwan; 43.6% in males, Korea; 33% in males and Japan (Kitamoto et al, 50% in males and the present study 43.2% in males)).…”
Section: Somatic Mutations In the Kcnj5 Gene And Their Gender-differementioning
confidence: 40%
See 1 more Smart Citation
“…Large multicenter studies have confirmed these findings and have shown that these mutations (G151R and L168R) account for 34%-47% of APAs in people of European ancestry (8)(9)(10) and 60%-77% of people of Asian ancestry (11)(12)(13)(14), with differences likely attributable to differences in disease definition. There is also a striking sex dimorphism in European and some Asian cohorts (8,10,11,15,16); European cohorts consistently show that these mutations account for 50%-60% of women with APAs, but only 20% of men, and KCNJ5 mutations are more prevalent in younger patients (8,10). A small numAldosterone-producing adenomas (APAs) are benign tumors of the adrenal gland that constitutively produce the saltretaining steroid hormone aldosterone and cause millions of cases of severe hypertension worldwide.…”
Section: Introductionmentioning
confidence: 77%
“…As a result, many patients are not diagnosed and do not receive optimal treatment. (11) C-metomidate PET-CT has been proposed as a noninvasive alternative (6). However, lower sensitivity and specificity, lack of availability in a typical outpatient setting, and high cost are potential concerns, and this procedure is not generally recommended by current guidelines (4).…”
Section: Introductionmentioning
confidence: 99%